1991
DOI: 10.1159/000177650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxysterol-Enriched Low-Density Lipoprotein on Endothelial Barrier Function in Culture

Abstract: High levels of plasma low-density lipoproteins (LDL) are known to be a risk factor for developing coronary artery disease although the specific mechanism involved is unknown. It may be related to effects of oxidized lipid components of LDL on vascular endothelial barrier function (EBF). This study addressed the hypothesis that LDL-associated products of cholesterol oxidation, oxysterols, decrease EBF resulting in increased penetration of blood components such as LDL into the arterial wall. LDL from human volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In vivo OS may partly be formed by reduction of cholesterol peroxides, as has been observed for hydroxy fatty acids. OS were first demonstrated to induce atherosclerosis in animals and to be toxic for vascular cells [16][17][18][19]. Epidemiological studies were conducted in Indian migrants in England who have a high incidence of atherosclerosis [19].…”
Section: Resultsmentioning
confidence: 99%
“…In vivo OS may partly be formed by reduction of cholesterol peroxides, as has been observed for hydroxy fatty acids. OS were first demonstrated to induce atherosclerosis in animals and to be toxic for vascular cells [16][17][18][19]. Epidemiological studies were conducted in Indian migrants in England who have a high incidence of atherosclerosis [19].…”
Section: Resultsmentioning
confidence: 99%
“…ChOx can induce endothelial dysfunction 12 or endothelial injury. 4 Previous studies have shown that certain ChOx and ChOxenriched LDL decreased vascular endothelial barrier functions, leading to increased transendothelial macromolecule transfer, 9,10,62,63 and that some ChOx strongly inhibit gap junction formation in fibroblasts. 64 Alternatively, apoptosis induced by ChOx leads to increased endothelial cell turnover, which is associated with increased endothelial transcytosis or permeability.…”
Section: Discussionmentioning
confidence: 99%
“…1 Studies specifically addressing this issue have shown that ChOx possess several characteristics that may promote atherosclerosis. These include cytotoxic/apoptotic potential to vascular cells such as fibroblasts, 2 endothelial cells, [3][4][5] and smooth muscle cells 6 -8 ; impairment of vascular endothelial barrier function 9,10 ; inhibition of endothelial NO release 11 and arterial relaxation 12 ; inhibition of cholesterol synthesis or utilization 13,14 ; perturbation of intracellular cholesterol trafficking [15][16][17] ; and activation of acyl CoA:cholesterol acyltransferase (ACAT) activity. 18,19 ChOx are abundant in oxidatively modified LDL (ox-LDL), 20 and high levels of circulating ChOx are found in rabbits fed a cholesterolcontaining diet.…”
mentioning
confidence: 99%
“…9 In addition, certain ChOx and ChOx-enriched LDL decrease vascular endothelial barrier function. 10,11 ChOx administered to animals by intravenous injection, oral feeding, and gavage have been reported to cause vascular injury. [12][13][14][15][16][17] However, the pharmacokinetics of ChOx are not well understood, nor are their vascular effects in the absence of hypercholesterolemia.…”
mentioning
confidence: 99%